STUDI KOMPARASI ANTARA MODEL PEMBELAJARAN DISCOVERY LEARNING DAN GROUP INVESTIGATION TERHADAP HASIL BELAJAR KIMIA SISWA - Julita Sari; Amrul Bahar; Dewi Handayani (ALOTROP, 2017)
The average students' chemical learning outcomes are still low, the low learning outcome is influenced by several factors, including students still consider that chemistry as one of the scary, difficult to understand and less interesting lessons. Therefore, the research wants to vary the learning process in the classroom by applying the learning model of Discovery Learning with Group Investigation model. This research was aimed to find out the students’ achievement differences of chemical subject by using Discovery learning and  Group Investigation model. The research is quasi experimental research. The population of this research were class X MIPA in SMAN 9 Bengkulu City, and the sample were X MIPA 2 and MIPA 3. This research using two experimental classes, that is class X MIPA 2 applying Group Investigation model and X MIPA 3 applying Discovery Learning model. Analysis of the data used is mean values, normality test, homogeneity test, and t-test. Post-test mean values for first experiment class is 78,12, but for second experiment class is 81,3. To determine whether the differences of student’s learning outcomes between both of experiment classes or not, we use t-test by using the differences between student’s pretest and posttest values, tcount > ttable (2,17 > 1,67). The result of this research showed that Ha accepted, in other words is a significant differences in learning outcomes of student’s applying Discovery Learning and Group Investigation model.